INTEGRATION HEALTH PROMOTION INTO HOSPITAL CARE: DEVELOPMENT OF HEALTH PROMOTING HOSPITAL (HPH) : THE BENEFITS, CHALLENGES AND THE IMPLEMENTATION FOR FUTURE HOSPITAL IN INDONESIA - MULIANINGSIH, NI PUTU BUDI (HEALTHY : Jurnal Inovasi Riset Ilmu Kesehatan, 2023)
This paper aims to provide a useful introduction of development and implementation of health promoting hospital (HPH), highlight the benefits, activities, barriers, strategies for implementation. It also points out the important of implementation for future hospitals in Indonesia and offer recommendations. The research design used literature study. Source of Data of this research is collected through journal text, books and data statistic and then it is analyzed with content analysis techniques. Based on literature study shows that its needs to develop and implement Health Promoting Hospital (HPH) which yield many benefits for hospital organization, management, patients and relatives, and community. In particular, the findings should have important implication and large contribution for development and successful implementation Health Promoting Hospitals in Indonesia particularly to Hospital management and staffs to enhance their understanding and awareness of the importance of reorienting Hospital service to becoming more health promoting and its implication to hospital and community, and engage them to implement HPH in Hospital daily activities. ABSTRACTTujuan penulisan artikel ini adalah mendeskripsikan tentang pengembangan Layanan Promosi Kesehatan kedalam layanan Rumah Sakit melalui pengembangan Promosi Kesehatan Rumah Sakit [HPH]. Data yang diperlukan dihimpun melalui kajian teks jurnal ,buku, dan data statistik, selanjutnya dianalisis menggunakan teknik analisi isi. Berdasarkan studi literatur menunjukkan bahwa perlunya membangun dan mengembangkan layanan Promosi Kesehatan RS dimana sangat bermanfaat unutk organisasi, management, pasien dan keluarga dan masyarakat sekitar. Khususnya hasil dari studi ini mempunyai implikasi dan memiliki kontribusi yang besar untuk berkembangnya and suksesnya pengembangan RS yang lebih mempromosikan kesehatan di Indonesia khususnya para manager dan staf untuk meningkatkan pemahaman mereka tentang pentingnya mengubah pandangan tentang layanan RS untuk lebih mengutamakan promosi kesehatan selain pelayanan dan menerapkan promosi kesehatan dalam rutinitas kerja mereka.